A mobicast routing protocol with carry‐and‐forward in vehicular ad hoc networks. (24th July 2012) - Chen, Yuh‐Shyan; Lin, Yun‐Wei
SUMMARY In vehicular networks, safety and comfort applications are two quite different kinds of applications to avoid the emergency traffic accident and enjoy the non‐emergency entertainment. The comfort application drives the challenges of new non‐emergency entertainments for vehicular ad hoc networks (VANETs). The comfort application usually keeps the delay‐tolerant capability; that is, messages initiated from a specific vehicle at time t can be delivered through VANETs to some vehicles within a given constrained delay time λ. In this paper, we investigate a new mobicast protocol to support comfort applications for a highway scenario in VANETs. All vehicles are located in a geographic zone (denoted as zone of relevance (ZOR)) at time t; the mobicast routing must disseminate the data message initiated from a specific vehicle to all vehicles that have ever appeared in ZOR at time t. This data dissemination must be performed before time t + λ through the carry‐and‐forward technique. In addition, the temporary network fragmentation problem is considered in our protocol design. Also, the low degree of channel utilization is kept to reserve the resource for safety applications. To illustrate the performance achievement, simulation results are examined in terms of message overhead, dissemination success rate, and accumulative packet delivery delay. Copyright © 2012 John Wiley & Sons, Ltd.